ALFABETIZAÇÃO E LETRAMENTO: uma análise a partir da prática docente de professoras alfabetizadoras da rede pública municipal de Imperatriz - MA, sob o prisma da transdisciplinaridade. - Sousa, Dijan Leal de (2024)
This thesis approaches the conception of literacy teachers about reading and writing skills in the literacy process in the light of the transdisciplinary methodology. Our main objective is to defend the thesis that the epistemological principles that underlie the modern scientific paradigm constitute the main obstacle that prevents a methodological practice, of teaching reading and writing, in which the literacy and reading and writing skill processes occur effectively and simultaneously. In order to achieve the proposed objective, we selected a bibliographic reference that provided the basis for the analysis of the data generated during the research, including, among others, the theoretical approaches of the following authors: Morin (1996; 2000; 2005; 2005; 2015); Santos (1988; 2002; 2014); Moraes (2008; 2011; 2015); Petraglia (1995; 2006; 2013); D'Ambrósio (1997; 2017); Nicolescu (1999; 2000; 2002; 2012); Soares (2004; 2014; 2015); Kleiman (1995; 2005; 2008; 2010); Tfouni (1988; 2005; 2013); and Freire (1982; 1987; 1996). The methodological course was guided by the type of case study research, following the qualitative approach. The data generation instruments used were: document analysis; non-participant observation; the semi-structured interview; and the autobiographical record. For data processing, we used content analysis as a way to interpret the information generated. As a result of the analyses, we emphasize that the teachers conceptually understand literacy and reading and writing skills as distinct and non-hierarchical processes, as well as recognizing a direct relationship between literacy practices and the use of diverse textual genres in the development of reading and writing activities. However, only one of the observed teachers carries out the processes simultaneously in her classes, because, in the practice of the other teachers, the literacy process prevails as the most relevant, being considered a prerequisite for the development of school literacy, since they consider that it is first necessary to master the technique of reading and writing and only then use it in practical situations. Based on these considerations, our thesis proposal starts from the premise that the epistemological principles of the modern scientific paradigm, disjunction and fragmentation, constitute one of the obstacles to the realization of a methodological practice of literacy and reading and writing skills, since the presence of these principles is still observed in the practices. In relation to transdisciplinarity, all the teachers presented some epistemological evidence that underlies this methodology, however the practices and attitudes manifested by them were developed unconsciously, since they are all unaware of the concept and epistemological principles of a transdisciplinary teaching practice.